Adopting Open Government in Local Development Planning: A Study on Bekasi Regency - Almaarif Almaarif; Ella Lesmanawaty Wargadinata (Magister Ilmu Administrasi Publik, 2022)
This paper aims to assess the adoption of open government principles in local government development planning. The study used constructivist research design which emphasizes using theory as guidance for analyzing the problems. Interview and document study techniques were used to collect data, while NVIVO version 12 plus was used in data processing and analysis. Research results showed that there has been a decline in community participation in development planning due to the perception that there are stark differences between contents of programs during the planning and implementation phases. Transparency in development planning is implemented in all programs at the subdistrict level, while at the district prioritized programs are deliberated in closely sessions that involve local government executives and the local legislature. As regards collaboration in development planning, results showed that pursuing and projecting own respective interests rather those of the public. Increasing open government principles in the development planning process requires intensive and regular communication and coordination among stakeholders, which makes ICT a key ingredient that should be form an integral part of the design and deployment process. This research recommends further research related to open government that should delve deeper into participation and transparency concepts as components of open government principles.